Maritime journeys of European opera in the Indonesian archipelago, 1835–1869 - Sugiyama, Akiko (SAGE Publications, 2019)
Professional performers of European opera began to arrive in Batavia in the 1830s. More performers set foot in Batavia in the next three decades and presented the often-matching selections of Italian and French opera. By the end of the 1860s the touring circuit of the itinerant performers encompassed leading port cities and towns, including Semarang, Surabaya and Padang. This article argues the coming of professional European opera to the Indonesian archipelago and greater maritime Asia was connected to the nineteenth-century operatic expansion in which the middling and intrepid singers transmitted current works of European opera to frontier regions. The journeys of the operatic pioneers to and from the Indonesian archipelago also mirrored an ongoing structural shift in coastal shipping from a business dominated by British merchant fleets to one serviced by the private firms under the contract of the Dutch East Indies government. © The Author(s) 2019.